1998
DOI: 10.1074/jbc.273.50.33566
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Heparin Cofactor II-Heparin and Heparin Cofactor II-Dermatan Sulfate Complexes

Abstract: Heparin cofactor II is a naturally occurring anticoagulant that acts by specifically inhibiting thrombin and is facilitated by the binding of glycosaminoglycans such as heparin and dermatan sulfate. In vivo, heparin cofactor II-glycosaminoglycan complexes dissociate, leaving the inhibitor less active in its ability to function as a component of the anticoagulation pathway. We have produced permanently activated heparin cofactor II molecules by covalent linkage to either heparin or dermatan sulfate. Covalent he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, because fibrin binds exosite I on thrombin, fibrinbound thrombin is more resistant to inhibition by HCII than by AT (32). Therefore, it has been reported that covalent conjugation of HCII and dermatan sulfate may be superior for the inhibition of clot-associated coagulant activity (33). Since the inhibition of thrombin by HCII activated with Ca-SP does not require the N-terminal acidic domain, Ca-SP-activated HCII may play an important role in the inhibition of fibrin-bound thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because fibrin binds exosite I on thrombin, fibrinbound thrombin is more resistant to inhibition by HCII than by AT (32). Therefore, it has been reported that covalent conjugation of HCII and dermatan sulfate may be superior for the inhibition of clot-associated coagulant activity (33). Since the inhibition of thrombin by HCII activated with Ca-SP does not require the N-terminal acidic domain, Ca-SP-activated HCII may play an important role in the inhibition of fibrin-bound thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…119 Recently, covalent complexes of DS and heparin with heparin cofactor II have been prepared and shown to be good inhibitors of thrombin. 120 These covalent complexes were prepared in a manner similar to covalent heparin-antithrombin complexes. 112 The heparin cofactor II-DS complex has fast bimolecular rate constants approaching diffusion limits ($10 7 M À1 sec À1 ) for reactions with thrombin.…”
Section: Other Carbohydrate-based Polymersmentioning
confidence: 99%
“…SERPINC1 can inhibit factor Xa and thrombin as a potent inhibitor of blood coagulation [41]. SERPIND1 is a plasma glycoprotein that inhibit thrombin specifically, which is activated by heparin or dermatan sulfate [42,43]. ANXA5 is a member of the annexin proteins as anticoagulant and antithrombotic protein [44].…”
Section: Discussionmentioning
confidence: 99%